Bovine serum miR-21 expression affected by mastitis. (March 2021) - Lai, Yu-Chang; Habiby, Gul Habib; Jasing Pathiranage, Chamila Chandana; Rahman, Md Mahfuzur; Chen, Hui-Wen; Husna, Al Asmaul; Kubota, Chikara; Miura, Naoki
Abstract: The expression levels of circulating microRNAs (miRNAs) can be affected by disease. The miRNA released from cells within exosomes can act as a remote communication tool and can participate in inflammatory response regulation. Therefore, circulating miRNA has the potential to be an indicator of local disease. The objective of this study was to investigate the serum level of bovine mastitis-related miRNAs. We found that miR-16 expression in serum was affected by hemolysis. The expression levels of miR-21 in serum were increased significantly in cows with mastitis compared with unaffected controls; however, the expression levels of miR-146a, miR-155, miR-222 and miR-383 in cows with mastitis were unchanged. We further verified the upregulation of miR-21 in the serum of cows with mastitis using a digital PCR system. Although the sensitivity and specificity of miR-21 in the serum to detect bovine mastitis was inferior to miRNA biomarkers in the milk, the significant increase of miR-21 in serum may reflect the impact of local inflammation on the systemic reaction. Highlights: miR-16 expression in serum was affected by hemolysis. miR-21 in serum were increased significantly in cows with mastitis. miR-21 in serum to detect mastitis was inferior to miRNA biomarkers in milk.